2021 21st International Conference on Solid-State Sensors, Actuators and Microsystems (Transducers) 2021
DOI: 10.1109/transducers50396.2021.9495471
|View full text |Cite
|
Sign up to set email alerts
|

A Thermal-Piezoresistive Self-Sustained Resonant Mass Sensor with High-Q (>95k) in Air

Abstract: This paper demonstrates, for the first time, a high sensitivity mass sensor based on thermal-actuation piezoresistive-detection coupled resonators with a selfsustained oscillation. In-plane-vibration resonators are actuated by thermal expansion and contraction of the nanobeams, while the vibration displacements are detected by changes in resistance. Due to the combination of the negative piezoresistive coefficient of the phosphorusdoped structural silicon layer and the thermal expansion/contraction effect, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…3 illustrates the principle of the thermal-electric-mechanical interaction. A more detailed description can also be found in [7]. The nanobeam plays the role of both actuating the resonator and detecting the movement as well.…”
Section: Device Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 illustrates the principle of the thermal-electric-mechanical interaction. A more detailed description can also be found in [7]. The nanobeam plays the role of both actuating the resonator and detecting the movement as well.…”
Section: Device Descriptionmentioning
confidence: 99%
“…The Q-factor is a measure of the energy dissipation in a specific working mode, and is a critical parameter to improve the signal to noise ratio (SNR) of force sensors, phase noise of oscillators and noise rejection of filters [6]. In previous work, we have already introduced a mass sensor with two coupled resonators using the thermal-piezoresistive principle with a Q-factor of ~95k in atmospheric environment [7]. However, associated with a high effective Q-factor, the startup time of the oscillator usually increases as well, limiting the applications that require periodic oscillator startup [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first miniature Si piezoresistive heat engine was reported in 2011 [1], a variety of self-sustained thermal-piezoresistive resonators or oscillators have been developed for mass sensing [2,3], Lorentz force measurement [4], gas detection [5], and signal amplification [6]. It was demonstrated that the thermalpiezoresistive effect is strong enough to initiate and maintain the mechanical oscillation of the resonator driven by direct current (DC), without the demand for any external alternating current (AC) source and amplifying circuitry.…”
Section: Introductionmentioning
confidence: 99%